Reinterpreting Qawwam through the Lens of Modern Muslim Feminism: A Critical Analysis in Islamic Discourse - Ms. Faryal Gul; Dr.Nazia Zamman (Journal of Religion and Society, 2025)
This study critically investigates the progressing interpretations of the Quranic term Qawwam (Qur’an 4:34) within modern Muslim feminist discourse, underlining how traditional interpretations emphasized male authority, are being challenged by feminist scholars promoting for ethical responsibility and gender justice. Using a mixed-methods approach grounded in qualitative analysis and textual explanation, the research explores both traditionalist and feminist readings of Qawwam, revealing the tension between traditionalist and existing egalitarian ideals. Prominent feminist such as Riffat Hassan and Fatima Mernissi are studied for their contributions to a gender-equitable hermeneutic grounded in the Islamic tradition. The results suggest that feminist reinterpretations not only contest patriarchal norms but also offer alternatives for integrating justice-oriented viewpoints into Islamic thought. While opposition to these re-readings continues within conventional circles, the study highlights the transformative potential of feminist scholarship in reforming Muslim understandings of gender, authority, and religious text. Keywords: Islamic Feminism; Qawwam; Gender Justice; Quranic Exegesis; Patriarchal Interpretation; Muslim Women; Feminist Hermeneutics